A Comparative Numerical Study on Piezoelectric Energy Harvester for Self‐Powered Pacemaker Application. Issue 1 (27th December 2017) - Kumar, Anuruddh; Kiran, Raj; Kumar, Sidhant; Chauhan, Vishal S.; Kumar, Rajeev; Vaish, Rahul
Abstract: This study proposes the design of a micro‐spiral‐shaped piezoelectric energy harvester that scavenges energy from blood pressure variation in the cardiac cycle. The harvester can be a miniaturized perennial source of power that could even eliminate the need for replacement of conventional batteries used in current pacemaker technology. The concept of a 25 µm thin spiral‐based piezoelectric energy harvester with a diameter of 6 mm satisfying the dimensional constraints has been proposed. A number of lead‐free materials have been used along with Pb[Zr x Ti1− x ]O3 (PZT‐5A) to compare the performance. The harvester has been designed in such a way that the natural frequency of the structure remains in the range of 1.1–1.3 Hz, which is equivalent to 66–78 heart beats min −1 of humans. The obtained alternating electric current from piezoelectric materials is converted into direct current. The maximum open‐circuit voltage obtained is ≈0.9 V, which is not sufficient for charging a pacemaker battery. Therefore, boost converter circuit is employed to step up the voltage. It is found that K0.475 Na0.475 Li0.05 (Nb0.92 Ta0.05 Sb0.03 )O3 (KNLNTS) has the best performance as compared to other materials under study. The boosted voltage obtained from KNLNTS is ≈6 and ≈7 V for 80 and 90% duty cycle, respectively, which are sufficient for pacemaker battery charging. Abstract : The present study proposes a novel spiral based piezoelectric energy harvester that harnesses the energy from the blood pressure variation in cardiac cycle. The main objective of the study is to eliminate the need for battery replacement. The electrical AC voltage obtained from the harvester is converted into DC and amplified using suitable circuits for practical application.